Creep Behavior of Frozen Sand. - Martin,R Torrence; Ting,John M; Ladd,Charles C (1981)
A total of 150 tests were run to evaluate the applicability of rate process theory, RPT, for frozen soil. Three creep test types: constant load into tertiary creep, temperature stage test under constant load, and stress stage test under constant temperature were used to obtain the parameters in the RPT equation. The soil was Manchester Fine Sand, MFS, at ice saturation of 40 and 100% and a constant relative density investigated over a temperature range -11 to -27 C with control of a given temperature to + or - 0.02 C.